Mainstreaming Local Food Species for Nutritional and Livelihood Security: Insights From Traditional Food Systems of Adi Community of Arunachal Pradesh, India - Singh, Ranjay K.; Bhardwaj, Rakesh; Singh, Anamika; Payum, Temin; Rai, Arvind K.; Singh, Anshuman; Wangchu, Lobsang; Upadhyay, Sanjay (Frontiers in Nutrition, 2021)
This study brings out the critical role of lesser-known local plant species in the food and livelihood security of Adi community in Arunachal Pradesh, India. Considering the women as a major custodian in knowledge and practices on foods, a total of 90 Adi women were selected from East Siang and Upper Siang districts of Arunachal Pradesh. Data were collected using combination of methods including recipe contest, focus group discussion, personal interviews and laboratory analyses. The results indicated that Adi women were able to identify 39 bio-culturally important species from a range of locally available plant species. Used alone or with other foods, these plants remain central to the Adi people’s cultural identity and livelihood security. In addition to improving food and nutritional security, these species accessed from different land use systems are also sold on the local markets to generate decent incomes. Of the species identified by Adi women, 28 were culturally shared and used frequently in food and ethnomedicine. Laboratory analyses of the selected 22 species revealed high levels of minerals and other nutrients, such as proteins and anti-oxidants, supporting their traditional use for health benefits. Our study results provide valuable insights to the researchers to explore the vast hidden potential of these and other similar species for improving nutritional well-being of local communities in marginal areas. Adequate policy support is needed to enable Adi and other such marginalized communities to cope with challenges being posed to traditional food systems. Keywords: Wild edible plants, bio-cultural knowledge, nutritional values, ethno-medicines, recipe contest, food and nutritional policies.